2016
DOI: 10.1002/2016ja023007
|View full text |Cite
|
Sign up to set email alerts
|

Auroral evidence of radial transport at Jupiter during January 2014

Abstract: We present Jovian auroral observations from the 2014 January Hubble Space Telescope (HST) campaign and investigate the auroral signatures of radial transport in the magnetosphere alongside contemporaneous radio and Hisaki EUV data. HST FUV auroral observations on day 11 show, for the first time, a significantly superrotating polar spot poleward of the main emission on the dawnside. The spot transitions from the polar to main emission region in the presence of a locally broad, bright dawnside main emission feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 71 publications
8
35
0
Order By: Relevance
“…With reference to previous works, this torus variability is likely associated with some combination of the following processes: energetic particle injection [e.g., Mauk et al , ], adiabatic heating by the dawn‐to‐dusk electric field [ Barbosa and Kivelson , ; Murakami et al , ], and/or heating by electromagnetic waves originally proposed for Io's downstream region [ Hess et al , ; Tsuchiya et al , ]. Although it is still unclear which process is the most feasible, the appearance of outer auroral emission at dusk after the declining phase of the transient aurora (Figure f) suggests that the energetic electron injection occurred after the transient aurora onset as reported from previous HST observations [ Gray et al , ]. Therefore, the transient dusk torus brightening on DOY142.50–142.65 is presumably associated with the injection.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…With reference to previous works, this torus variability is likely associated with some combination of the following processes: energetic particle injection [e.g., Mauk et al , ], adiabatic heating by the dawn‐to‐dusk electric field [ Barbosa and Kivelson , ; Murakami et al , ], and/or heating by electromagnetic waves originally proposed for Io's downstream region [ Hess et al , ; Tsuchiya et al , ]. Although it is still unclear which process is the most feasible, the appearance of outer auroral emission at dusk after the declining phase of the transient aurora (Figure f) suggests that the energetic electron injection occurred after the transient aurora onset as reported from previous HST observations [ Gray et al , ]. Therefore, the transient dusk torus brightening on DOY142.50–142.65 is presumably associated with the injection.…”
Section: Discussionmentioning
confidence: 84%
“…The image taken on DOY140 is shown as a representative for the quiet period (Figure b). Between 02:17:42 and 03:02:12 (DOY142.10–142.13) on DOY142 (Figures c–e), a dawn storm, which is suggestive of dawnside tail reconnection and planetward return flow [ Cowley et al , ; Clarke et al , ], was evident at System III longitude of 180°–260° less than in the main oval (Figures c–e) as observed during the 2014 HST campaign [ Kimura et al , ; Badman et al , ; Gray et al , ]. This exposure time corresponds to the onset timing of the transient aurora in the Hisaki data.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Vasyliūnas reconnection is the most plausible candidate for the initiation of the transient aurora, as suggested by the energetic event. Gray et al () actually indicated that during the transient aurora, an auroral spot merged into the dawn storm from high latitudes, which is suggestive of the reconnection return flow in the outer magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The auroral signature of this current system generally looks like a partially complete ring, called the main emission [ Ballester et al , ; Grodent et al , ], which only accounts for about half of the total emitted power in the UV [e.g., Nichols et al , ]. Equatorward of the main oval are diffuse, arc‐shaped, or compact emissions associated with pitch angle diffusion [ Radioti et al , ] and/or hot plasma injections in the inner/middle magnetosphere [ Mauk et al , ; Bonfond et al , ; Dumont et al , ; Gray et al , ]. In the same region, the electromagnetic interaction between the moons Io, Europa, and Ganymede produces auroral footprints in the form of localized spots sometimes followed by a tail (see review by Bonfond []).…”
Section: Introductionmentioning
confidence: 99%